Travel writing as an instrument of cultural heritage promotion - Potočnik Topler, Jasna (Annales. Series historia et sociologia, 2024)
This study contributes to the research literature through its approach to equipping tourism content creatives who are entering the professions of destination image communication with platform expertise alongside cooperation and co-creation leadership. Productive skills for travel writers and social media content producers in tourism are significant in the co-creation of sustainable tourist experiences since they are interactive and participative. The two purposes of this study are to implement and improve the dialogue journaling process as a re-usable methodology. The new 3-step processual research methodology is explained through a case study with stakeholders and project leaders in Brežice, Slovenia. The paper contributes to pragmatic tourism management concerns and practice by reporting findings from a real-world process project on cultural heritage that provides a re-usable solution.
Keywords: co-creation; cooperation; cultural heritage promotion; dialogue journaling; metoda zapisovanja dialoga; potopisno pripovedništvo; promocija kulturne dediščine; razvoj turizma; sodelovanje; soustvarjanje; stakeholder engagement; tourism development; travel writing; vključevanje deležnikov